Experimental and numerical investigation of the frequency-domain characteristics of impact load for AUV during water entry. (15th April 2020) - Shi, Yao; Gao, Xingfu; Pan, Guang
Abstract: Autonomous underwater vehicles (AUVs) are subjected to a very large impact load during the water-entry process, which may damage the structure of the vehicle and affect its motion trajectory. In this paper, five kinds of models with different nose shapes are tested under different water-entry velocities and angles, and the impact acceleration signals are obtained by a sensor. First, the accuracy of the experimental data is verified by comparison with the velocity obtained by the high-speed camera. Then, the ensemble empirical mode decomposition (EEMD) method combined with modal analysis is used to analyse the acceleration signal composition. Subsequently, a numerical simulation model based on the arbitrary Lagrangian Eulerian (ALE) method to describe the water-entering process of the vehicle is established, and the accuracy and capability of the numerical algorithm is verified by comparison with the experimental data. Finally, the frequency-domain characteristics of the impact load are analysed through the shock response spectrum (SRS) method. The result shows that the maximum acceleration shock spectrum of the impact load is related to the peak pulse width of the impact load and independent of the peak value. The smaller the pulse width is, the larger the inflection point frequency and magnification of the shock response spectrum are. The inflection point frequency of the shock response spectrum usually corresponds to the second-order bending natural frequency of the vehicle. The conclusions in this paper will be useful for the design and analysis of the water-entry impact structure of AUVs. Highlights: The composition of the water entry impact acceleration is obtained by the EEMD method. The frequency domain characteristics of the impact load are analyzed. The ALE method for simulating the water entry problem was built and validated.